Carter's conversion the hardening of American defense policy - Auten, Brian J., 1969-; ebrary, Inc. (Columbia : University of Missouri Press, 2008)
"Examining Carter's dramatic shift from advocating defense budget cuts early in his administration to supporting development of the MX missile and modernization of NATO's Long-Range Theater Nuclear Force by the end of his presidency, the author argues, counter to common interpretations, that the shift was a "self-correcting" policy change in response to the prevailing international military environment"--Provided by publisher.
Originally presented as the author's thesis (Ph. D.)--2004.
Includes bibliographical references (p. 311-332) and index.
Electronic reproduction.
Keywords: Carter, Jimmy, -- 1924- -- Political and social views; North Atlantic Treaty Organization -- Military policy; National security -- United States -- Decision making; MX (Weapons system) -- History; Deterrence (Strategy) -- United States -- History; United States -- Foreign relations -- 1977-1981.; United States -- Military policy -- Decision making; Electronic books